Productivity and quality of Formosa and Solo papaya over two harvest seasons - Barros, Fabíola Lacerda de Souza; Kuhlcamp, Karin Tesch; Arantes, Sara Dousseau; Moreira, Sarah Ola (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the productivity and quality of papaya fruits (Carica papaya) of the Solo (12 genotypes) and Formosa (9 genotypes) heterotic groups over two harvest seasons. The experiment was conducted under field conditions in the municipality of Pinheiros, in the state of Espírito Santo, Brazil, in a randomized complete block design. Ten morpho-agronomic and physicochemical variables of the fruits were measured in winter (210–300 days after planting) and summer (450–540 days after planting). The data were subjected to the combined analysis of variance, to the breakdown of the genotype x environment interactions, and to the grouping of means by the Scott-Knott test. Although harvest season affected the evaluated characteristics, it did not alter the classification of the genotype. In the Solo group, the 'H 36-45' and 'UC 15' hybrids stand out due to their greater productivity, fruit weight, and soluble solids contents. In the Formosa group, the Rubi Incaper 511 cultivar shows greater productivity, higher number of fruits for commercial use, and lower number of deformed fruits over both evaluated harvest seasons.